Stability Analysis of High-Order Iterative Learning Control for a Class of Nonlinear Switched Systems - Xuhui Bu; Fashan Yu; Ziyi Fu; Fuzhong Wang (Abstract and Applied Analysis)
This paper considers the stability of high-order PID-type iterative learning control law for a class of nonlinear switched systems with state delays and arbitrary switched rules, which perform a given task repeatedly. The stability condition for the proposed high-order learning control law is first established, and then the stability is analyzed based on contraction mapping approach in the sense of λ norm. It is shown that the proposed iterative learning control law can guarantee the asymptotic convergence of the tracking error for the entire time interval through the iterative learning process. Two examples are given to illustrate the effectiveness of the proposed approach.